2005
DOI: 10.3748/wjg.v11.i18.2754
|View full text |Cite
|
Sign up to set email alerts
|

Blood platelet and monocyte activations and relation to stages of liver cirrhosis

Abstract: Platelet and monocyte activation plays an important role in LC. Platelet activation stage does not influence monocyte activation and production of plt aggregates with monocytes in LC. With LC development, thrombocytopenia may be the result of plt consumption in platelet-monocyte aggregates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…Similar results were reported by Camps et al [26] . However, Panasiuk et al [27] reported a de- Our results also revealed a significant negative correlation between vitamin D and MCP-1. This supports the role of decreased vitamin D in inflammation and fibrosis.…”
supporting
confidence: 60%
“…Similar results were reported by Camps et al [26] . However, Panasiuk et al [27] reported a de- Our results also revealed a significant negative correlation between vitamin D and MCP-1. This supports the role of decreased vitamin D in inflammation and fibrosis.…”
supporting
confidence: 60%
“…All of the seven patients with liver disease suffered from invasive aspergillosis, which reflected their immunocompromised status and the presence of additional risk factors for S. maltophilia colonization, such as antibiotic therapy. As such, those seven patients are at risk of infections precipitated by the significant impairment of the neutrophil defence mechanism, frequent use of corticosteroids and invasive procedures, and malnutrition (Panasiuk et al, 2005;Cheruvattath & Balan, 2007;Falcone et al, 2011;Fishman, 2011;Barchiesi et al, 2015). However, to the best of our knowledge, our study is the first description of an association between co-infection by A. fumigatus and S. maltophilia and patients with liver disease.…”
Section: Discussionmentioning
confidence: 71%
“…Blood platelets, besides hemostatic properties, have the features of inflammatory cells [15,16]. Activated platelets present on their surfaces molecules CD62P and CD63 that transmit stimulation signals when in contact with other cells (platelets, monocytes, and lymphocytes) [17].…”
Section: Discussionmentioning
confidence: 99%